Characterization of RAD9 of Saccharomyces cerevisiae and evidence that its function acts posttranslationally in cell cycle arrest after DNA damage. - Weinert, T A (1990)
In eucaryotic cells, incompletely replicated or damaged chromosomes induce cell cycle arrest in G2 before mitosis, and in the yeast Saccharomyces cerevisiae the RAD9 gene is essential for the cell cycle arrest (T.A. Weinert and L. H. Hartwell, Science 241:317-322, 1988). In this report, we extend the analysis of RAD9-dependent cell cycle control. We found that both induction of RAD9-dependent arrest in G2 and recovery from arrest could occur in the presence of the protein synthesis inhibitor cycloheximide, showing that the mechanism of RAD9-dependent control involves a posttranslational mechanism(s). We have isolated and determined the DNA sequence of the RAD9 gene, confirming the DNA sequence reported previously (R. H. Schiestl, P. Reynolds, S. Prakash, and L. Prakash, Mol. Cell. Biol. 9:1882-1886, 1989). The predicted protein sequence for the Rad9 protein bears no similarity to sequences of known proteins. We also found that synthesis of the RAD9 transcript in the cell cycle was constitutive and not induced by X-irradiation. We constructed yeast cells containing a complete deletion of the RAD9 gene; the rad9 null mutants were viable, sensitive to X- and UV irradiation, and defective for cell cycle arrest after DNA damage. Although Rad+ and rad9 delta cells had similar growth rates and cell cycle kinetics in unirradiated cells, the spontaneous rate of chromosome loss (in unirradiated cells) was elevated 7- to 21-fold in rad9 delta cells. These studies show that in the presence of induced or endogenous DNA damage, RAD9 is a negative regulator that inhibits progression from G2 in order to preserve cell viability and to maintain the fidelity of chromosome transmission.